O combate ao crime organizado e o garantismo social - Pereira, Camila Bonafini (2019)
The aim of this work is to establish a proportionality judgment between the Legal Garantism Theory, developed by Luigi Ferrajoli, and the fundamental rights protected by it, in view of the procedural instruments necessary to combat organized crime, which are considered by the Italian jurist as violators of citizen’s rights. In order to do so, it is necessary to study fundamental rights from birth until they are enshrined in the Constitutions and represent an axiological system that influences the entire legal system and which must be seen from two perspectives: as a prohibition of state’s intervention and as imperatives of state’s tutelage. Having analyzed fundamental rights as a prohibition of state’s intervention, it appears that the Legal Garantism Theory, developed by Luigi Ferrajoli, aims to protect fundamental rights, considering them only as a ban on state intervention. However, it should be noted that, in order for fundamental rights to be realized in their completeness, a negative action by the State is not enough, and it is imperative that they also be observed as imperatives of tutelage, what means, as a right in face of the State to which he is liable so others do not intervene in such a way as to violate fundamental rights. At this point, it must be observed that, due to globalization, society has suffered big changes, which have strengthened organized crime, responsible for serious violations of fundamental rights throughout the world, and must therefore be fighted. The characteristics of this criminality have brought about the need to rethink the penal system, creating institutes suited to their combat, which, however, suffer severe criticism from the doctrine, which considers them anti-guarantees and violators of fundamental rights. In this context, in face of an apparent collision between fundamental rights and their dimensions, it is necessary to use the principle of proportionality in its dual face, that is, as a limiting factor to the limitations imposed on fundamental rights, and also as a form to control insufficient action by the State to solve it, always in order to ensure that the essential core of fundamental rights remain untouched by the state’s measures to combat criminal organizations